In Vivo Fluxes in the Ammonium-Assimilatory Pathways in Corynebacterium glutamicum Studied by (15)N Nuclear Magnetic Resonance - Tesch, M. (American Society for Microbiology, 1999)
Glutamate dehydrogenase (GDH) and glutamine synthetase (GS)–glutamine 2-oxoglutarate-aminotransferase (GOGAT) represent the two main pathways of ammonium assimilation in Corynebacterium glutamicum. In this study, the ammonium assimilating fluxes in vivo in the wild-type ATCC 13032 strain and its GDH mutant were quantitated in continuous cultures. To do this, the incorporation of (15)N label from [(15)N]ammonium in glutamate and glutamine was monitored with a time resolution of about 10 min with in vivo (15)N nuclear magnetic resonance (NMR) used in combination with a recently developed high-cell-density membrane-cyclone NMR bioreactor system. The data were used to tune a standard differential equation model of ammonium assimilation that comprised ammonia transmembrane diffusion, GDH, GS, GOGAT, and glutamine amidotransferases, as well as the anabolic incorporation of glutamate and glutamine into biomass. The results provided a detailed picture of the fluxes involved in ammonium assimilation in the two different C. glutamicum strains in vivo. In both strains, transmembrane equilibration of 100 mM [(15)N]ammonium took less than 2 min. In the wild type, an unexpectedly high fraction of 28% of the NH(4)(+) was assimilated via the GS reaction in glutamine, while 72% were assimilated by the reversible GDH reaction via glutamate. GOGAT was inactive. The analysis identified glutamine as an important nitrogen donor in amidotransferase reactions. The experimentally determined amount of 28% of nitrogen assimilated via glutamine is close to a theoretical 21% calculated from the high peptidoglycan content of C. glutamicum. In the GDH mutant, glutamate was exclusively synthesized over the GS/GOGAT pathway. Its level was threefold reduced compared to the wild type.